SHOPPER DECISION PROCESS TOWARD ONLINE MARKETPLACE CASE STUDY: BUKALAPAK - Maharani, Actualita; Fachira, Ira (Journal of Business and Management, 2018)
Abstract.The growth of using internet is increasing rapidly, people also actively use the internet for the selling and shopping purposes. In previous year of 2017, many retailers have expanded their business activity in digital marketing. E-commerce companies have to take the opportunity to enhance their potential consumers by differentiating their marketing strategy againts the competitors. The method of this study uses quantitative method. The quantitative method would be done by distributing online questionnaires to the people who have used Bukalapak at least once. The respondents are collected for the total of 783 people which the data is analyzed using structural equation model (SEM) to define the relationship among variables. The findings discuss perceived benefits of search significantly affects external search effort, external search effort significantly affects perceived risk, overall deal evaluation is significantly affected by perceived benefits of search and perceived risk, and overall deal evaluation significantly affects willingness to buy. To sum up, the objective of exploring shopper decision process in e-commerce marketplace is answered by the findings. Therefore, some results could be renew the previous study about e-commerce marketplace. The recommendation was proposed to give insight for the e-commerce business especially for Bukalapak to improve their marketing strategy.Keywords: E-commerce C2C, Digital marketing, Bukalapak, Shopper behavior, Shopper decision processÂ Â Â